Deep Learning Based Natural and Social Sciences (IPAS) Learning Design to Strengthen Scientific Literacy in Madrasah Ibtidaiyah - Ahmad Arif Musyafa'; Ahmad Fahrudin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This study aims to develop a deep learning based Natural and Social Sciences (IPAS) learning design to improve the scientific literacy of students at a Madrasah Ibtidaiyah (Islamic primary school). The research employed a Research and Development (R&D) approach using the ADDIE model, comprising analysis, design, development, implementation, and evaluation stages. The study was conducted at MI Roudlotul Mubtadiin Bendo, Pare District, Kediri Regency, Indonesia, involving fourth- and fifth-grade teachers and 34 students. Data were collected through classroom observations, teacher interviews, expert validation sheets, student response questionnaires, and scientific literacy tests. The scientific literacy instrument was validated prior to implementation to ensure its validity and reliability in measuring students' competencies, including scientific explanation, interpretation of evidence, and problem-solving in contextual situations. The developed learning design was also evaluated by content and instructional-design experts, and the product met the feasibility criteria following minor revisions prior to implementation. The implementation results indicate that the developed learning design was practical and effectively facilitated student engagement through environmental exploration, collaborative discussion, and presentation activities. Student responses showed positive perceptions of the learning process, indicating that the product was practical and easy to implement in classroom settings. In terms of effectiveness, students' average scientific literacy score increased from 64.2 on the pre-test to 81.5 on the post-test, indicating improved learning outcomes and achievement of the expected competency criteria. The findings suggest that the developed deep learning-based IPAS learning design is valid, practical, and effective for enhancing scientific literacy among Madrasah Ibtidaiyah students through contextual, exploratory, and meaningful learning experiences.